Differential Progression of Regional Hippocampal Atrophy in Aging and Parkinson’s Disease - Uribe, Carme; Segura, Barbara; Baggio, Hugo C.; Campabadal, Anna; Abos, Alexandra; Compta, Yaroslau; Marti, Maria Jose; Valldeoriola, Francesc; Bargallo, Nuria; Junque, Carme (Frontiers in Aging Neuroscience, 2018)
Hippocampal subfields have different vulnerability to the degenerative processes related to aging, amnestic mild cognitive impairment and Alzheimer’s disease, but the temporal evolution in Parkinson’s disease (PD) is unknown. The purposes of the current work are to describe regional hippocampal changes over time in a sample of PD patients classified according to their baseline cognitive status and to relate these changes to verbal memory loss. T1-weighted images and verbal memory assessment were obtained at two separate time points (3.8±0.4 years apart) from 28 PD with normal cognition (PD-NC), 16 PD with mild cognitive impairment and 21 healthy controls. FreeSurfer 6.0 automated pipeline was used to segment the hippocampus into 12 bilateral subregions. Memory functions were measured with Rey’s Auditory Verbal learning test (RAVLT). We found significant reductions in cornu ammonis (CA1) over time in controls as well as in PD subgroups. Right whole-hippocampal volumes showed time effects in both PD groups but not in controls. PD-NC patients also displayed time effects in the left hippocampal tail and right parasubiculum. Regression analyses showed that specific hippocampal subfield volumes at time 1 predicted almost 60% of the variability in RAVLT delayed-recall score decline. Changes in several hippocampal subregions also showed predictive value for memory loss. In conclusion, CA1 changes in PD were similar to those that occur in normal aging, but PD patients also had more decline in both anterior and posterior hippocampal segments with a more pronounced atrophy of the right hemisphere. Hippocampal segments are better predictors of changes in memory performance than whole-hippocampal volumes.